Contribution of Banks on Agricultural Development in Bangladesh (Global Journal of Management and Business Research, 2021)
Most of the cases, the determinants of agricultural development are crops, purchase and installation of irrigation equipment, livestock, marketing of agricultural goods fisheries, poverty alleviation and income generating activities. Banks also disburse loan on each of these sectors. So banks plays an important role on agricultural development in Bangladesh. Timely and adequate flow of agricultural credit can meet farmers demand to enhance agricultural productivity. The aim of this paper is to determine the contribution of banks on agricultural development in Bangladesh. This study collected time series data from various sources and analyze the contribution of agricultural credit of banks in Bangladesh.
Keywords: agriculture; agricultural credit; agricultural development; bangladesh